The educational structure of students' sports training in the framework of physical education classes at a higher educational institution - Rakovetskу A.I. ,; Ponomarev V.V. ,; Akhankin V.N. ,; Tokarev D.А. , (Theory and Practice of Physical Culture, 2025)
Introduction. The modern process of physical education of students in non-physical education universities is aimed at the physical training of young people and the formation of general physical education competencies, which in general does not motivate the student contingent to systematically engage in physical education and sports. In general, an "average" process of physical education is organized, aimed at minimally maintaining physical activity, without taking into account the individual abilities of those involved. In addition, there is a decrease in the number of teaching and practical hours for physical education of students in the country's universities, where up to 70% or more of classes are held only in the 1st and 2nd years, and in the third year – at best, electives. We also note that up to 20% of the teaching hours for physical education are transferred to a lecture course, which does not provide students with the necessary physical activity. The best theory of physical education is practice. The need to introduce a sports-specific approach into physical education of students will help increase students' motivation, realize their individual motor potential, and form a sustainable sports culture, which will allow young people to cultivate their chosen sport in their future professional and social life. At the same time, the Minister of Sports of Russia M.V. Degtyarev identified one of the main tasks for improving the physical education and sports movement in the country through the development of a sports-oriented approach in physical education of student youth in Russian universities.